2010
DOI: 10.1016/j.baae.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A question of origin: Where and how to collect seed for ecological restoration

Abstract: Native plant species are routinely planted or sown in ecological restoration projects, but successful establishment and survival depend on where and how seeds are collected. Research suggests that it is important to use locally adapted seeds. Local populations often show a home-site advantage and non-local genotypes may be maladapted to local environmental conditions. Furthermore, intraspecific hybridisation of local and non-local genotypes may have a negative impact on the genetic structure of local populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
238
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(270 citation statements)
references
References 79 publications
5
238
1
5
Order By: Relevance
“…Therefore, field studies will be necessary to resolve the adaptive effects of the field phenotypes associated with the observed variations in germination, survival and growth traits reported here. Also, non-local genotypes may suffer from maladaptation to the local environment resulting in a lower fitness (Vander Mijnsbrugge et al 2010), so reciprocal transplant experiments (RTEs) are needed to test how the species would respond to changing climates.…”
Section: Survival and Growth Differences Between Provenances And Sitesmentioning
confidence: 99%
“…Therefore, field studies will be necessary to resolve the adaptive effects of the field phenotypes associated with the observed variations in germination, survival and growth traits reported here. Also, non-local genotypes may suffer from maladaptation to the local environment resulting in a lower fitness (Vander Mijnsbrugge et al 2010), so reciprocal transplant experiments (RTEs) are needed to test how the species would respond to changing climates.…”
Section: Survival and Growth Differences Between Provenances And Sitesmentioning
confidence: 99%
“…In certain circumstances, the multiplication of native seeds for ecological restoration in a farm setting becomes necessary when harvesting large volumes of seeds directly from natural habitats would damage the reproductive capabilities of the local populations [10][11][12], or donor communities of sufficient size have disappeared due to human impact [13]. Moreover, sourcing local seeds and maintaining the genetic variability of the native populations is key to ecosystem conservation through improvement in long-term restoration trajectories [3,7,11,14]. Based on national acts occurring in a few European countries [15,16], the newly released International Standards for the Practice of Ecological Restoration [17], and other published works [2,13], restoration practitioners should avoid using seed mixtures that include non-native species, seed of unknown origin or seed sourced from genetically uniform populations.…”
Section: Introductionmentioning
confidence: 99%
“…Within Europe, trade and use of herbaceous seeds are less regulated when compared to forest reproductive material [3]. More attention should be given to grasslands conservation, as they are counted among both the most species-rich vegetation types in Europe [4,5] and among the most extensively degraded and least protected habitats at both the European [4] and global scale, making them identifiable as a biome at risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…Once this phase has passed, seeds that were not in the original mix (such as Chenopodium album, as found in this study) were able to colonise the substrates (Madre et al 2014). However some invaders may be of the same speciespossibly with a more hardy advantage over the commercially bought seeds (Vander Mijnsbrugge et al 2010) -resulting in reduced individual plant numbers over time but a constant number of species maintained within the substrates. It should be noted that this was a short-term study and that the number of species may be reduced in subsequent years, as found by Dunnett et al (2008), Nagase & Dunnett (2010) and Benvenuti (2014) as some species become more dominant.…”
Section: Discussionmentioning
confidence: 99%